Understanding Unemployment among Tertiary Educated Youth - Khushbu, Seema Rani; Jyoti, Santosh Sharma (Archives of Current Research International, 2024)
Youth unemployment remains a critical global issue, with far-reaching economic and social implications. This research explores the multifaceted causes of unemployment among 200 tertiary educated youth at Chaudhary Charan Singh Haryana Agricultural University, Hisar. From the selected colleges, a list of students both undergraduate and postgraduate experiencing unemployment for the last 3-4 years was prepared. From the list a proportionate sample of 200 unemployed youth (comprising 100 graduates and 100 postgraduates) was systematically chosen from the entire educated youth population across the colleges of CCS Haryana Agricultural University, Hisar encompassing I.C College of Home Science, College of Basic Sciences & Humanities, College of Agriculture and College of Agriculture Engineering & Technology. Therefore, a proportionate sample of 27 graduate students and 45 postgraduate students from COHS, 28 postgraduate students from the College of Basic Sciences and Humanities, 50 graduate and 21 postgraduate students from the College of Agriculture, and 23 graduate and 6 postgraduate students from the College of Agriculture Engineering and Technology who were unemployed for the last 3–4 years were selected to comprise a total 200 sample size. Addressing the gap in existing literature, the study categorizes the causes into four key dimensions: structural, educational, individual, and private sector-related causes. The objective of the study is to analyze how these causes contribute to unemployment and their interrelated effects. A descriptive research design was employed, with data collected through a structured questionnaire. The analysis reveals that structural causes, such as high competition for limited job opportunities and the increasing demand for specialized skills, are significant barriers to employment. Educational mismatches, including misalignment between academic qualifications and industry requirements, further intensify the issue. Individual challenges, like limited job search skills, and private sector constraints, such as low wages and restrictive hiring practices, also contribute to unemployment. The findings underscore the complexity of youth unemployment and highlight the need for targeted policy interventions. By addressing these diverse causes, the study suggests reforms in education, skill development programs, and enhanced private sector engagementas essential strategies to improve youth employability and foster inclusive economic growth.